2011
DOI: 10.1245/s10434-011-1609-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intra-tumoral Infiltrating Macrophages and Regulatory T Cells Is an Independent Prognostic Factor in Gastric Cancer after Radical Resection

Abstract: Association of intratumoral Mφ and Tregs is a promising independent predictor for survival in advanced gastric cancer. The results suggested that a combination of concomitant stimulation of intratumoral Mφ and Tregs may be an effective strategy for treatment of patients with advanced gastric cancer after radical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 32 publications
2
80
0
3
Order By: Relevance
“…Furthermore, it has been reported that Tregs together with TAMs form a special niche which promotes tumour progression and metastasis,23 but high co-densities of macrophages and Tregs with metastasis was not found in this study. Co-stimulation of CD68 and FOXP3 might also be a possible component of an effective treatment strategy against cancer 29. Therefore, we assessed the simultaneous high densities of the macrophage markers with FOXP3 staining in relation to prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that Tregs together with TAMs form a special niche which promotes tumour progression and metastasis,23 but high co-densities of macrophages and Tregs with metastasis was not found in this study. Co-stimulation of CD68 and FOXP3 might also be a possible component of an effective treatment strategy against cancer 29. Therefore, we assessed the simultaneous high densities of the macrophage markers with FOXP3 staining in relation to prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…CD68, an antigen expressed by cytoplasmic lysosomes in M1 and M2 macrophages26 (Novacastra, CC1 24’, mouse polyclonal, 1:1600); CD163, a transmembrane protein highly expressed by M2 macrophages27 (Novacastra, CCL 24’, mouse polyclonal, 1:400); CD206, a mannose receptor expressed on also M2 macrophages28 (Sigma Aldrich, CC1, rabbit monoclonal, MRC1, 1:500); and FOXP3, a protein expressed by Tregs functioning to suppress the immune system (Abcam, mouse monoclonal, 1:2000) were stained. We additionally investigated densities of macrophage markers and FOXP3, as FOXP3 recruitment by macrophages has been reported,21 22 and because TAMs and Treg co-expression is a possible component of an effective treatment strategy against cancer 29…”
Section: Methodsmentioning
confidence: 99%
“…In the end, we reviewed 58 studies encompassing 16 different cancer types (Table 1), including bladder (19), breast (21)(22)(23)(24)(25)(26)(27)(28), cervical (29,30), colorectal (12,(31)(32)(33)(34)(35)(36)(37)(38)(39), endometrial (40)(41)(42), gastric (14,(43)(44)(45)(46), head and neck (47), hepatocellular (48)(49)(50)(51)(52), lung (53,54), melanoma (55)(56)(57)(58), mesothelial (59), oral (4,(60)(61)(62)(63), ovarian (2,3,…”
Section: Introductionmentioning
confidence: 99%
“…[77], отметившими ухудшение отдаленных результатов лечения при высокой плотности Foxp3 + регуляторных Т-лимфоцитов. В ряде исследований высокая плотность Foxp3 + T-reg лимфоцитов бы-ла, напротив, связана с улучшением выживаемости пациентов с раком желудка [58,78,79].…”
Section: Foxp3unclassified
“…Ряд авторов отметили, что высокая плотность опухолеин-фильтрирующих макрофагов является фактором, улучшающим прогноз при раке желудка [79]. Однако большинство исследова-ний свидетельствует о том, что высокая плотность макрофагов связана с факторами неблагоприятного прогноза и ухудшением отдаленных результатов лечения больных раком желудка [33,80,81].…”
Section: Foxp3unclassified